Dietary Phytoestrogen Intake and Cognitive Status in Southern Italian Older Adults - Francesca Giampieri; Justyna Godos; Giuseppe Caruso; Marcin Owczarek; Joanna Jurek; Sabrina Castellano; Raffaele Ferri; Filippo Caraci; Giuseppe Grosso (Biomolecules, 2022)
Background: Aging society faces significant health challenges, among which cognitive-related disorders are emerging. Diet quality has been recognized among the major contributors to the rising prevalence of cognitive disorders, with increasing evidence of the putative role of plant-based foods and their bioactive components, including polyphenols. Dietary polyphenols, including phytoestrogens, have been hypothesized to exert beneficial effects toward brain health through various molecular mechanisms. However, the evidence on the association between dietary phytoestrogen intake and cognitive function is limited. The aim of this study was to investigate the association between phytoestrogen intake and cognitive status in a cohort of older adults living in Sicily, Southern Italy. Methods: Dietary information from 883 individuals aged 50 years or older was collected through a validated food frequency questionnaire. Cognitive status was assessed through the Short Portable Mental Status Questionnaire. Results: The highest total isoflavone (including daidzein and genistein) intake was inversely associated with cognitive impairment compared to the lowest (odds ratio (OR) = 0.43, 95% confidence interval (CI): 0.20–0.92). Higher intake of total lignans and, consistently, all individual compounds (with the exception of secoisolariciresinol) were inversely associated with cognitive impairment only in the unadjusted model. Conclusions: A higher intake of phytoestrogens, especially isoflavones, was associated with a better cognitive status in a cohort of older Italian individuals living in Sicily. Taking into account the very low intake of isoflavones in Italian diets, it is noteworthy to further investigate selected populations with habitual consumption of such compounds to test whether these results may be generalized to the Italian population.